Marketing Mix Sebagai Upaya Penguatan Pembiayaan Mudharabah - Lisa Yuni Lestari; M Nanang Febrianto; M Aqim Adlan; Johan Dwi Sutikno (PELITA NUSA TENGGARA, 2026)
Baitul Maal wat Tamwil, through its mudharabah financing products, seeks to support the economic empowerment of the lower-middle class through effective marketing strategies. However, in practice, BMT still faces various challenges, such as limited promotional efforts, suboptimal market segmentation, and a product portfolio that lacks competitiveness. This initiative aims to provide educational opportunities and guidance on implementing a marketing mix strategy through the 4Ps framework to increase the volume of mudharabah financing at BMT Sahara Kauman. The implementation of this initiative relies on a service-learning approach focused on coaching sessions. Furthermore, the outcomes at the end of the activity demonstrated a significant improvement in financing services through the development of mudharabah product features, the establishment of more competitive profit-sharing ratios, the expansion of service networks, the strengthening of Sharia branding, and community-based promotion. These results indicate that the mentoring activities regarding the marketing mix strategy have been successfully implemented. The proactive approach and the increase in the value of mudharabah financing demonstrate that employees are now better prepared to reach a broader community, which is beneficial for the more effective and sustainable development of the BMT.